Indigenous Peoples Engagement to Mainstream Local Politics: a Southern Philippines Narrative - Joy Melyn L. Jayma (Institut Pemerintahan Dalam Negeri (IPDN), 2017)
This study focuses on a specific indigenous community in Mindanao, Philippines – the Bukidnon Tribe. The Bukidnon Tribe is one of the well-documented and well-researched tribes in the region and is also a recipient of various projects in the past. This paper primarily aims to answer the question, whether the Bukidnon Tribe have mainstreamed their presence in local politics. With the implementation of the Indigenous Peoples’ Rights Act (IPRA), the traditional political institutions of the different tribes are now nationally recognized. With that in place, this study has the following specific questions: a) how engaged is the Bukidnon tribe in local politics, b) how are the traditional political institutions of the Bukidnon tribe survive in relation to engagement to mainstream politics, and c) what are the political influences and effects of the past projects given to the tribe. Results show that through the IPRA, which mandated an IP representative for every local government unit (LGU) in areas with IP population, the indigenous communities are assured of representation. Because of presence of the IP representatives in LGUs, the other members of the tribe are encouraged to further recognize and participate in mainstream political activities such as voting in elections and consultation with regards to policy formulation. The results also indicated that the tribe recognizes the value and importance of their traditional political institutions, thus, they themselves strive hard for its preservation despite all the external factors brought by the projects. From the results, it is suggested that educating the mainstream society about the rich political culture of the tribe as a method to ease the penetration of the IPs to local politics as there will be greater respect for cultural diversity.